Coupling of Photonic Crystal Surface Modes - Melike Behiye Yücel (Advances in Condensed Matter Physics)
Guiding and evanescent coupling properties of surface modes bound to the interfaces of two-dimensional photonic crystals in close proximity are numerically demonstrated. Interacting photonic crystals are composed of silicon pillars in air, where their outermost layers facing each other are annular. Surface modes are identified through supercell band structure computations, while their excitation by the electromagnetic waves through a perpendicular insertion waveguide is demonstrated using finite-difference time-domain simulations. Lifting the degeneracy between the surface modes as a consequence of bringing two identical photonic crystal surfaces to a sufficient distance results in evanescent coupling in a beating manner whose beat length linearly varies between 10 and 20 periods up to a frequency at which both surface modes travel with the same group velocity. The surface mode coupling phenomenon could be employed either to enhance sensitivity or to reduce device size in bio/chemical sensor applications since the effective travelling length of surface waves increases by about 3.5 times due to evanescent coupling.